2015
DOI: 10.3390/chromatography2020253
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Mitragynine and 7-Hydroxymitragynine in Human Urine by LC-MS/MS

Abstract: Kratom is a tree planted in Southeast Asia, including Thailand, Malaysia, Myanmar (Burma) and elsewhere in the region. A long history of usage and abuse of kratom has led to the classification of kratom as a controlled substance in its native Thailand and other Southeast Asian countries. However, kratom is not controlled in the United States, and the wide availability of kratom on the Internet and in the streets has led to its emergence as an herbal drug of misuse. With the increasing popularity of kratom, eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
5
0
1
Order By: Relevance
“…A rapid and effective method for quantification of mitragynine and 7-hydroxymitragynine compounds in human urine matrix was reported. Correlation coefficients greater than 0.99 were obtained for both mitragynine and 7hydroxymitragynine compounds in the previous study [21]. In the current study, mass spectrometry part was emphasized with mass spectrum and mass fragments information.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…A rapid and effective method for quantification of mitragynine and 7-hydroxymitragynine compounds in human urine matrix was reported. Correlation coefficients greater than 0.99 were obtained for both mitragynine and 7hydroxymitragynine compounds in the previous study [21]. In the current study, mass spectrometry part was emphasized with mass spectrum and mass fragments information.…”
Section: Introductionmentioning
confidence: 54%
“…In the previous study, it was focused on the method development and validation using LC-MS/MS [21]. A rapid and effective method for quantification of mitragynine and 7-hydroxymitragynine compounds in human urine matrix was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Mitragynine was stable in plasma at room temperature for 6 hr (Parthasarathy et al, 2010) and in refrigerated urine (pH not specified) for 14 days (Fu et al, 2015). Papsun reported that mitragynine was stable in blood containing sodium fluoride and potassium oxalate for 7 days at room temperature and up to 30 days when refrigerated or frozen.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several methods have been developed to rapidly identify kratom alkaloids in human urine [161][162][163][164][165] ; this approach can be especially helpful in deciding the treatment course of an unresponsive patient presenting with suspected kratom toxicity. Fu et al 166 developed a sensitive and specific LC-MS/MS method for the efficient detection of MG and 7-OH-MG in urine. Several previously conducted studies also described the analysis of MG and 7-OH-MG in human urine, using various chromatographic methods.…”
Section: Mitragynine Detection Methodsmentioning
confidence: 99%